Comparative studies of AJG049, a novel Ca(2+) channel antagonist, on voltage-dependent L-type Ca(2+) currents in intestinal and vascular smooth muscle - Hashimoto, M (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: Antagonists of Ca(2+) channels reduce contraction of intestinal smooth muscle but also affect vascular smooth muscle. We have therefore examined the effects of AJG049, a newly synthesized antagonist for regulation of gut motility, on voltage-dependent L-type Ca(2+) channels, in vascular and intestinal smooth muscle, comparing AJG049 with two other Ca(2+) channel antagonists, verapamil and diltiazem. EXPERIMENTAL APPROACH: Affinities of AJG049 for various types of voltage-dependent Ca(2+) channels were examined by binding studies. Effects of AJG049 on voltage-dependent inward Ca(2+) (or Ba(2+)) currents (I(Ca) or I(Ba)) in dispersed smooth muscle cells from guinea-pig ileum, colon and mesenteric artery were measured using conventional whole-cell configurations. KEY RESULTS: In binding studies, AJG049 showed a high affinity for the diltiazem-binding site of L-type Ca(2+) channels. In whole-cell configuration, AJG049 suppressed I(Ca) in ileal myocytes, with concentration-, voltage-and use-dependencies. AJG049 shifted the steady-state inactivation curve of I(Ca) to the left. The order of potency to inhibit I(Ca) in ileal myocytes was AJG049>verapamil>diltiazem. AJG049 also suppressed I(Ba) in guinea-pig mesenteric arterial myocytes, showing concentration- and voltage-dependencies and the potency order for this action was also AJG049>verapamil>diltiazem. For the relative ratio of K(i) values between ileal and mesenteric arterial myocytes, the order was AJG049>diltiazem≫verapamil. CONCLUSIONS AND IMPLICATIONS: These results show that AJG049 inhibits L-type Ca(2+) channels mainly through the diltiazem-binding site(s). From our results, AJG049 showed a little selectivity for these Ca(2+) channels in intestinal smooth muscle.